ANALISIS STRATEGI PEMASARAN MOBIL PICK UP PADA DEALER SUZUKI RESTU MAHKOTA KARYA KABUPATEN SUKABUMI - Liliawati, Lia (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This Suzuki Restu Mahkota Karya (RMK) Dealer in Sukabumi Regency is engaged in trading and service companies. This marketing strategy is very important for the continuity of the company and to be able to increase product sales so that the sales profit will increase as much as possible. From the report on the sales of Pick Up cars from January to December 2017, for the City and Sukabumi Regency areas with the implementation of this marketing strategy, the sales of Pick-up cars that are in great demand for the City area are Gunung Puyuh District, Warudoyong, Baros, Cibeureum . While for the Regency area are Cibadak, Parungkuda, Jampang Kulon, Nagrak, Sukabumi, Cicurug and Surade sub-districts. And for the types of Pick Up cars that many interested in are Futura PU Wide Deck, APV PU, and PU PS APV